Acute toxicity of formalin to seabass (lates calcarifer) fry. - Pascual, Florendo Conrado P
Two trials of 96 h each were done to determine the median lethal concentration (LC50) of formalin to seabass (Lates calcalifer) fry. The LC50 computed after 12, 24, 48, 72, and 96 h were 272.9, 258.6, 256.9, 240.9, and 239.2 ppm, respectively. Toxic reactions exhibited by the fish include unbalanced and sudden jerky swimming motions, rapid opercular movements, distribution in the different water levels, surfacing, and change in pigmentation.